Computing an ensemble of variational data assimilations using its mean and perturbations. (8th February 2017) - Lorenc, Andrew C.; Jardak, Mohamed; Payne, Tim; Bowler, Neill E.; Wlasak, Marek A.
Abstract : We show how to replace an ensemble of variational data assimilation minimizations by minimizations for the ensemble mean and the perturbations from it. Tests using the Met Office system show that this Mean–Pert method can give practically identical results at much reduced cost. This makes it a good candidate component when designing a cost‐effective system for hybrid ensemble‐variational data assimilation for numerical weather prediction.